King Vision video laryngoscope for severe post burn contracture neck: an encouraging experience - Qazi Ehsan Ali; Obaid Ahmed Siddiqui; Syed Hussain Amir; Sarfaraz Ahmad; Shaista Jamil (Brazilian Journal of Anesthesiology, 2017)
Background and objectives: Managing the airway of post burn contracture of the neck has always been challenging to anesthesiologists as it limits the alignment of oro-pharyngo-laryngeal axes because of functional and anatomical deformities that occur as a result of long standing contractures. Here the role of the King Vision video laryngoscope which is the latest in the series of video laryngoscope has been evaluated for such patients. Case report: A 35 year old male patient with post burn contracture of neck was scheduled for release of the contracture. As the patient had had fixed flexion deformity of the neck we did not attempt the conventional laryngoscopy. Instead we opted for King Vision video laryngoscope. Conclusion: We therefore conclude that King Vision videolaryngoscope can be used for difficult airway situations like post burn contracture of neck. Resumo: Justificativa e objetivos: O manejo de vias aéreas em contratura de pescoço após queimadura sempre foi um desafio para os anestesiologistas, pois a contratura limita o alinhamento do eixo orofaringolaringeo devido às deformidades funcionais e anatômicas que ocorrem como resultado de contraturas de longa duração. Relato de caso: Paciente do sexo masculino, 35 anos de idade, com contratura do pescoço após queimadura foi programado para liberação da contratura. Como o paciente estava com deformidade fixa em flexão no pescoço, não tentamos a laringoscopia convencional e optamos por usar o vídeo laringoscópio King Vision. Conclusão: O videolaringoscópio King Vision pode ser usado em situações de via aérea difícil como a contratura de pescoço após queimadura. Keywords: King Vision, Contracture neck, Intubation, Palavras-chave: King Vision, Contratura do pescoço, Intubação